Resolvin D5 Protects Female Hairless Mouse Skin from Pathological Alterations Caused by UVB Irradiation - Priscila Saito; Ingrid C. Pinto; Camilla C. A. Rodrigues; Ricardo L. N. de Matos; David L. Vale; Cristina P. B. Melo; Victor Fattori; Telma Saraiva-Santos; Soraia Mendes-Pierotti; Mariana M. Bertozzi; Ana P. F. R. L. Bracarense; Josiane A. Vignoli; et al. (MDPI AG, 2024)
Resolvin D5 (RvD5) is a lipid mediator that has been reported to present anti-inflammatory and pro-resolution properties. Evidence also supports its capability to enhance reactive oxygen species (ROS) production during bacterial infections, which would be detrimental in diseases driven by ROS. The biological activity of RvD5 and mechanisms against UVB irradiation skin pathology have not been investigated so far. Female hairless mice were treated intraperitoneally with RvD5 before UVB stimulus. RvD5 reduced skin edema in a dose-dependent manner as well as oxidative stress by increasing antioxidants (endogenous tissue antioxidant scavenging of cationic radical, iron reduction, catalase activity and reduced glutathione levels) and decreasing pro-oxidants (superoxide anion and lipid peroxidation). RvD5 antioxidant activity was accompanied by enhancement of Nrf2, HO-1 and NQO1 mRNA expression. RvD5 reduced the production of IL-1β, TNF-α, TGF-β, and IL-10. RvD5 also reduced the inflammatory cell counts, including mast cells and neutrophils/macrophages. The reduction of oxidative stress and inflammation resulted in diminished matrix metalloproteinase 9 activity, collagen degradation, epidermal thickening and sunburn cell development. Therefore, this study demonstrates, to our knowledge, the first body of evidence that RvD5 can be used to treat UVB skin pathology and unveils, at least in part, its mechanisms of action.